Discussion on Hundru fall as a knick point, Iharkhand, India - Sinha, Malavika (Acta Geographica Debrecina Landscape & Environment series, 2021)
Subarnarekha River lies in the vicinity to the Ranchi mega lineament zone of Jharkhand State. This river links  the Tamar Porapahar shear zone and North Singhbhum shear zone. The Hundru falls is the sudden and abrupt drop of elevation (longitudinal profile) of upstream of river Subarnarekha. The basic aim of this paper is to assess the Hundru falls as a perfect citation of an upstream knick point in Indian context. This paper covers the knick point formation of upstream of the Subarnarekha river. This upper catchment is more diversified in the terms of metamorphic and igneous rocks. This zone has crossed a long path with diversified lithospheric adjustment with epirogenic upliftment.